Effect Of Personalized Instruction Strategy On Pupils’ Academic Achievement In Numeracy In Ilorin West Local Government Area Of Kwara State - Arisekola Salman, Azeez; Ajibola Elisha, Ojo (International Journal of Educational Research & Social Sciences, 2024)
This study focused on effect of personalized instructional strategy on pupils academic achievement in Ilorin West Local Government Area of Kwara State. The study adopted pre-test post-test control group quasi-experimental research design. A factorial design of 2X2 was adopted for the study. The population comprises of all public and private primary schools pupils. The sample size were four primary three classes. First, all the schools were divided into two strata (Private and Public), and Purposive sampling technique was used to select (2) public and (2) private schools using intact class. Three research instruments were used titled: Pupils’ Numeracy Achievement Test (PNAT) with two treatment packages, Instructional Guide for Personalized Instruction (IGPI) and Instructional Guide for Conventional Method (IGCM). Instruments were subjected to face and content validity by some selected numeracy. Test re-test method of reliability was used. Thereafter, Pearson Product Moment Correlation (PPMC) was used to determine the reliability index of  (r=.71). Three research hypotheses were formulated and tested at 0.05 level of significance. The demographic data of the participants, were analyzed using frequency counts, mean, and percentage while the research hypotheses were tested, using analysis of co-variance (ANCOVA) at 0.05 level of significance. The finding revealed among others that there was a significant main effect of treatment on pupils’ academic achievement in Numeracy in Ilorin West Local Government, Kwara State (F (1; 129) = 10.175, P< 0.05). Those exposed to Personalized Instruction (15.726) performed significantly higher than those exposed to conventional method (14.667). Based on the findings of this study, it can be explicitly stated that personalized instructional strategy can enhance better performance in Numeracy than the traditional method of teaching and learning. Recommendation were made among others, Numeracy teachers should be enlightened on the effectiveness of personalized instructional strategy on pupils’ academic performance in Numeracy.